Involvement of CesA4, CesA7-A/B and CesA8-A/B in secondary wall formation in Populus trichocarpa wood. (18th June 2019) - Abbas, Manzar; Peszlen, Ilona; Shi, Rui; Kim, Hoon; Katahira, Rui; Kafle, Kabindra; Xiang, Zhouyang; Huang, Xiong; Min, Douyong; Mohamadamin, Makarem; Yang, Chenmin; Dai, Xinren; et al.
Abstract: Cellulose synthase A genes ( CesA s) are responsible for cellulose biosynthesis in plant cell walls. In this study, functions of secondary wall cellulose synthases PtrCesA4, PtrCesA7-A/B and PtrCesA8-A/B were characterized during wood formation in Populus trichocarpa (Torr. & Gray). CesA RNAi knockdown transgenic plants exhibited stunted growth, narrow leaves, early necrosis, reduced stature, collapsed vessels, thinner fiber cell walls and extended fiber lumen diameters. In the RNAi knockdown transgenics, stems exhibited reduced mechanical strength, with reduced modulus of rupture (MOR) and modulus of elasticity (MOE). The reduced mechanical strength may be due to thinner fiber cell walls. Vessels in the xylem of the transgenics were collapsed, indicating that water transport in xylem may be affected and thus causing early necrosis in leaves. A dramatic decrease in cellulose content was observed in the RNAi knockdown transgenics. Compared with wildtype, the cellulose content was significantly decreased in the PtrCesA4, PtrCesA7 and PtrCesA8 RNAi knockdown transgenics. As a result, lignin and xylem contents were proportionally increased. The wood composition changes were confirmed by solid-state NMR, two-dimensional solution-state NMR and sum-frequency-generation vibration (SFG) analyses. Both solid-state nuclear magnetic resonance (NMR) and SFG analyses demonstrated that knockdown of PtrCesA s did not affect cellulose crystallinity index. Our results provided the evidence for the involvement of PtrCesA4, PtrCesA7-A/B and PtrCesA8-A/B in secondary cell wall formation in wood and demonstrated the pleiotropic effects of their perturbations on wood formation.